Peran Word of Mouth dan Digital Review terhadap Keputusan Seleksi : Studi pada Rumah Sakit Swasta di Jawa Tengah - Mahardika, Rosliana; Setyawan, Antonius Ary Setyawan (Jurnal Bisnis dan Kewirausahaan, 2025)
This study investigates the influence of word of mouth (WOM) and digital reviews on patients’ decisions to select private hospitals in Indonesia, a context where healthcare quality information is limited and informal sources are increasingly pivotal. Drawing on theories of social influence and dual processing, the study develops a model integrating WOM, digital reviews, and their interaction in shaping hospital selection decisions. Using a quantitative, explanatory approach, data were collected from 217 respondents who had recently chosen private hospitals based on either WOM or online reviews. A structured questionnaire was administered, and data were analyzed using Structural Equation Modeling (SEM) via SmartPLS 4.0. The results indicate that both WOM (β = 0.39, p < 0.001) and digital reviews (β = 0.41, p < 0.001) significantly influence hospital choice. Moreover, digital reviews moderate the WOM effect (β = 0.21, p = 0.005), reinforcing its impact when both sources align. Robustness tests confirm model stability, and multi-group analysis shows consistent effects across gender. The study contributes to the literature by examining the joint impact of WOM and e-WOM in healthcare—a sector marked by high trust requirements—and provides strategic implications for hospital marketers to manage both interpersonal and digital reputation channels cohesively. These findings offer context-specific insights for private hospital administrators in developing countries navigating increasingly digital patient behaviors.